High-performance polyimide copolymer fibers derived from 5-anino-2-(2-hydroxy-4-aminobenzene)-benzoxazole: Preparation, structure and properties. (15th August 2018) - Dai, Xuemin; Bao, Feng; Jiao, Long; Yao, Haibo; Ji, Xiangling; Qiu, Xuepeng; Men, Yongfeng
Abstract: A series of high-performance polyimide copolymer (co-PI) fibers containing phenylenebenzoxazole moiety with one hydroxyl group are synthesized based on the copolymerization of 3, 3′, 4, 4′-biphenyl tetracarboxylic dianhydride (BPDA) with two diamine monomers, namely, p -phenylenediamine ( p -PDA) and 5-anino-2-(2-hydroxy-4-aminobenzene)-benzoxazole ( p -mHBOA), through a two-step method. The molar ratio of p -PDA/ p -mHBOA varies from 10/0 to 0/10. Influences of the p -mHBOA moieties on the thermal stability, crystal structure, crystal orientation, microvoid morphology, and mechanical properties are systemically investigated. Fourier transform infrared results confirm that intra/inter molecular hydrogen bonds come from the OH group and nitrogen atom of the benzoxazole group and/or OH group and the oxygen atom of the carbonyl group of cyclic imide. The glass transition temperatures ( T g s) of co-PI fibers are in the range of 290 °C–325 °C. The prepared fibers show excellent thermal stabilities, and their T 5% is within 528 °C–542 °C in air. Two-dimensional wide-angle X-ray diffraction spectra indicate that homo-PI and co-PI fibers present a regularly arranged polymer chains along the fiber axial direction. Moreover, the ordered molecular packing along the transversal direction of fibers is destroyed by the copolymerization. Small-angle X-ray scattering results show that co-PI fibers with optimal mechanical properties exhibit the shortest average length ( L ) and the smallest radius ( R ¯ ) of microvoids. When the p -mHBOA/ p -PDA molar ratio is 5/5, the fracture strength and initial modulus can reach approximately 30.31 cN/dtex (4.40 GPa) and 894.88 cN/dtex (129.8 GPa), respectively. The relationship between structure and mechanical properties is also discussed. Graphical abstract: Image 1 Highlights: A series of polyimide copolymer fibers containing phenylenebenzoxazole moiety with one hydroxyl group have been successfully prepared. The introduction of hydroxyl groups can form strong inter-/intramolecular hydrogen bonding among polymer chains. Mechanical properties of PI fibers have been remarkably enhanced.